Communication, the Heart of a Relationship: Examining Capitalization, Accommodation, and Self-Construal on Relationship Satisfaction - De Netto, Priscilla Maria; Quek, Kia Fatt; Golden, Karen Jennifer (Frontiers in Psychology, 2021)
The study of processes that enrich positive relationships has been an under-researched area within positive psychology practice. The way an individual responds in conflicts (accommodation response) and towards a partner’s disclosure of good news (capitalization response) has been linked to relationship quality. Although the accommodation and capitalization communication processes are part and parcel of our everyday lives, the two processes have been examined separately and dominated by the Western perspectives in past research. Prior work has suggested that Western and Asian cultures differ in expressing and perceiving beneficial communication behaviours. Yet, it is still unclear which accommodation and capitalization responses matter the most from an Asian lens. To date, there is no research examining these interconnected variables simultaneously in Asia, specifically in Malaysia. In this study, two forms of communication processes, (1) accommodation and (2) capitalization, were explored concurrently to disentangle the unique associations and influence on relationship satisfaction. This study also sought to understand the moderating effects of culture in terms of interdependent self-construal on the link between these two communication processes and relationship satisfaction. Responses of 139 Malaysians in dating relationships between the age of 18 to 30 years (Mage = 23.15) were collected through online surveys. An active and constructive reaction was captured as the most favourable response through both the capitalization and accommodation processes. Prominently, an active-constructive capitalization response bore the strongest influence on relationship satisfaction above and beyond other responses. A passive and constructive response was revealed only fruitful for disclosures of positive news and not during conflicts. Conversely, in the destructive paradigm, passive-destructive responses were the most detrimental factor in relationships compared to other destructive responses. The results also uncovered that interdependent self-construal did not moderate the two forms of communication processes; however, the findings discovered unexpected individual and cultural variations. This pioneering study is a noteworthy addition to the positive psychology literature from an Asian standpoint. It highlights the significance of not only protecting relationships through better conflict management but also enriching relationships by capitalizing on the positive aspects of a couple’s life, ultimately providing a greater holistic insight into cultivating flourishing lives.